2017
DOI: 10.18632/oncotarget.22041
|View full text |Cite
|
Sign up to set email alerts
|

Reduced m6A mRNA methylation is correlated with the progression of human cervical cancer

Abstract: The m6A mRNA methylation involves in mRNA splicing, degradation and translation. Recent studies have revealed that reduced m6A mRNA methylation might promote cancer development. However, the role of m6A mRNA methylation in cervical cancer development remains unknown. Therefore, we investigated the role of m6A methylation in cervical cancer in the current study. We first evaluated the m6A mRNA methylation level in 286 pairs of cervical cancer samples and their adjacent normal tissues by dot blot assay. Then the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 32 publications
1
74
0
Order By: Relevance
“…Consistently, it was observed that m 6 A obtained low expression in cervical cancer, and the reduced m 6 A level was associated with higher FIGO stage and recurrence. 45 Further investigation showed that down-regulation of m 6 A level induced by interference of METTL3 and METTL14 or overexpression of FTO and ALKBH5 could promote cervical cell proliferation, and vice versa. Herein, we conclude the possible mechanisms about m 6 A-associated proteins in other cancers as follows.…”
Section: A Modification Inhibits the Tumour Progressionmentioning
confidence: 98%
“…Consistently, it was observed that m 6 A obtained low expression in cervical cancer, and the reduced m 6 A level was associated with higher FIGO stage and recurrence. 45 Further investigation showed that down-regulation of m 6 A level induced by interference of METTL3 and METTL14 or overexpression of FTO and ALKBH5 could promote cervical cell proliferation, and vice versa. Herein, we conclude the possible mechanisms about m 6 A-associated proteins in other cancers as follows.…”
Section: A Modification Inhibits the Tumour Progressionmentioning
confidence: 98%
“…[4][5][6][7] Recent literatures have validated the correlation between m6A and human cancers including hepatocellular carcinoma, breast cancer, pancreatic cancer and cervical cancer. [8][9][10][11] However, the clinical values and biological roles of m6A-related genes in HB have not been reported. METTL3 is an RNA methyltransferase that can modify the biological occurrence, decay and translation control of mRNA by m6A.…”
Section: Introductionmentioning
confidence: 99%
“…The potential involvement of m 6 A in cancer is reinforced by the enriched proteoglycans in cancer KEEG pathway (22 genes, PBenjamini = 2.43╳10 -2 ). This is not surprising as there is increasing evidence demonstrating its regulatory roles in different cance r [20,[64][65][66][67][68][69][70]. Another enriched KEGG pathways are Protein processing in the endoplasmic reticulum (20 genes, PBenjamini = 2.37╳10 -2 ) and Lysosome pathway (18 genes, PBenjamini = 6.31╳10 -3 ), both of which are protein processing pathways.…”
Section: Functional Significant M 6 A-regulated Genes Identified By Hmentioning
confidence: 96%